PENGARUH PURSED LIP BREATHING TERHADAP PENURUNAN PERSEPSI DYSPNEA PADA PASIEN PPOK DI PAVILIUN CEMPAKA RSUD JOMBANG - Rozi, Fahrur (LPPM STIKes Bahrul Ulum Jombang, 2018)
Shortness of breath (Dypsnea) is a condition that describes the sensation of shortness of breath, or difficulty breathing and shortness of breath are often associated with heart or respiratory disease, and is characterized by airflow obstruction, This study aimed to determine the effect of the decrease pursed Lip Breathing Dyspnea perception in COPD patients.This study design using quasy Experimental studies were conducted in 32 patients with COPD in the Pavilion Cempaka Jombang General Hospital in February-March 2018.Respondents were divided into 2 groups, 16 groups of PLB 16 control group. Data analysisuse Independent t test Test,In the test statistic Independent t test PLB has a significant value of p = 0.000 (p <0.05), the PLB has a significant value of p = 0.000 (p <0.05).Nurses can use the PLB therapy as an alternative therapy for reducing the perception of dyspnea in patients with COPD.